New amide-chloride phases in the Li-Al-N-H-Cl system: Formation and hydrogen storage behaviour - Fernández Albanesi, Luisa Francisca (2016)
New amide-chloride phases were successfully synthesized by mechanical milling of the LiNH2-AlCl3 mixture at a molar ratio of 1:0.11 and further heating at 150 °C under argon (0.1 MPa) or under hydrogen pressure (0.7 MPa). Powder X-ray diffraction measurements as a function of milling time increase revealed that the milling of the LiNH2-0.11AlCl3 mixture results in the formation of a FCC solid solution with an excess of LiNH2. Subsequent heating of the LiNH2-0.11AlCl3 sample ball milled for 5 hours at 150 °C under argon or under hydrogen induces the appearance of an amide-chloride phase isostructural with cubic Li4(NH2)3Cl. This Li-Al-N-H-Cl phase transforms progressively into the trigonal phase after prolonged heating at 300 °C under hydrogen pressure. The thermal behaviour of the amide-chloride without and with LiH addition displays dissimilar decomposition pathways. The decomposition of amide-chloride alone involves the formation of ammonia and hydrogen from 120 to 300 °C. Conversely, the amide-chloride material in the presence of LiH only releases hydrogen avoiding the emission of ammonia. The resultant material is able to be rehydrogenated under moderate conditions (300 °C, 0.7 MPa H2), providing a new reversible hydrogen storage system.